Ternary hydrotalcites in the multicomponent synthesis of 4H-pyrans - Nope Vargas, Eliana Rocio (2020)
Lamellar double hydroxides (LDH) with double divalent cations were synthesized by the co-precipitation method and studied in the multicomponent synthesis of 4H-pyrans. The solids obtained were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR), N2 adsorption isotherms, and thermogravimetric analysis (TGA). The XRD patterns confirmed the formation of LDHs in which the incorporation of Ni2+ or Co2+ improves their crystalline and textural properties. The results of catalytic activity showed that the synthesis of 4H-pyrans is favored in solvent-free conditions with the LDH–Ni catalyst, avoiding calcination processes. In addition, it was found that hydrotalcite with double divalent cations can conduct this reaction through multicomponent synthesis or by the Michael addition reaction, which can be performed by different types of basicity that depend on the composition of another divalent cation in the brucite layer or a calcination process.